2012
DOI: 10.1016/j.molcel.2012.04.014
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Ligase XIAP Recruits LUBAC for NOD2 Signaling in Inflammation and Innate Immunity

Abstract: Nucleotide-binding and oligomerization domain (NOD)-like receptors constitute a first line of defense against invading bacteria. X-linked Inhibitor of Apoptosis (XIAP) is implicated in the control of bacterial infections, and mutations in XIAP are causally linked to immunodeficiency in X-linked lymphoproliferative syndrome type-2 (XLP-2). Here, we demonstrate that the RING domain of XIAP is essential for NOD2 signaling and that XIAP contributes to exacerbation of inflammation-induced hepatitis in experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
404
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 351 publications
(432 citation statements)
references
References 40 publications
18
404
1
1
Order By: Relevance
“…[166][167][168] Notably, RIP2 is required to mediate all of the in vivo host responses to MDP. 169 The ubiquitination of RIP2 is a critical step in mediating activation of these NOD2 pathways, especially activation of NFkB, 164,165 and a number of E3 ubiquitin ligases, including TRAF6, 164 cIAP and XIAP proteins [170][171][172] and ITCH 173 have been proposed to catalyse ubiquitination of RIP2. However, other studies have questioned the importance of many of these E3 ligases in the context of ubiquitinating RIP2 and activating NFkB.…”
Section: Rip2 and Nod Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…[166][167][168] Notably, RIP2 is required to mediate all of the in vivo host responses to MDP. 169 The ubiquitination of RIP2 is a critical step in mediating activation of these NOD2 pathways, especially activation of NFkB, 164,165 and a number of E3 ubiquitin ligases, including TRAF6, 164 cIAP and XIAP proteins [170][171][172] and ITCH 173 have been proposed to catalyse ubiquitination of RIP2. However, other studies have questioned the importance of many of these E3 ligases in the context of ubiquitinating RIP2 and activating NFkB.…”
Section: Rip2 and Nod Signallingmentioning
confidence: 99%
“…However, other studies have questioned the importance of many of these E3 ligases in the context of ubiquitinating RIP2 and activating NFkB. Thus the ubiquitination of RIP2 is intact in TRAF6-deficient cells, 165 pharmacological depletion of cIAP1 and cIAP2 has no effect on RIP2 ubiquitination 171 and ITCHmediated ubiquitination of RIP2 is associated with negative regulation of RIP2-mediated NFkB signalling. 173 We have recently described a key role for the E3 ubiquitin ligase Pellino3 in directly ubiquitinating RIP2 and mediating NOD2 downstream signalling, including its activation of NFkB and protective effects in colitis 174,175 (Figure 4).…”
Section: Rip2 and Nod Signallingmentioning
confidence: 99%
“…1d). To confirm the absence of activity towards RIPK1, which is also associated with the NODosome 17 and plays an important role in other innate immune signalling pathways, we performed an in vitro kinase assay with immunoprecipitated RIPK1 from immortalized mouse BMDMs. Addition of ATP to RIPK1 promoted rapid auto-Ser/Thr phosphorylation and this autophosphorylation was blocked by the RIPK1 inhibitor Nec-1.…”
Section: Wehi-345 Is a Potent And Selective Inhibitor Of Ripk2mentioning
confidence: 99%
“…RIPK2 plays a central role in the NOD signalling pathway and cells deficient in RIPK2 fail to mount a cytokine response upon NOD stimulation 14,15 . We and others have shown that upon NOD stimulation, RIPK2 is ubiquitylated by inhibitor of apoptosis (IAP) proteins, and this recruits the linear ubiquitination assembly complex (LUBAC), which is essential for downstream signalling [16][17][18] .…”
mentioning
confidence: 99%
“…19 Intriguingly, XIAP (X-linked Inhibitor of Apoptosis) was also recently observed to be present in the NOD2 signaling complex. 20 Unlike cIAP1/2, XIAP primarily synthesizes K63-and K48-independent atypical polyubiquitin chains on RIP2, which enable the incorporation of LUBAC into the NOD2 signaling complex. RIP2 was later uncovered to be the prime substrate of LUBAC in NOD2 signaling through quantitative proteomics analysis of the components obtained from M1-Ub-affinity purification.…”
Section: Modulation Of Innate Immune Signaling By the Ubiquitin Systemmentioning
confidence: 99%